The Divider Assay is a high-throughput pipeline for aggression analysis in Drosophila - Budhaditya Chowdhury (Nature Portfolio, 2021)
Chowdhury et al. develop the Divider Assay, which is a simplified experimental procedure that allows Drosophila researchers to perform aggression analysis for a long period of time and in complete darkness. They find a peak in fighting during the middle of the day. This pipeline is expected to facilitate high-throughput screening for aggression.